Antibiotic-taking experiences of undergraduate college students. - Aronson, Barbara S (Journal of the American Academy of Nurse Practitioners, 2006)
Purpose: The purpose of this qualitative descriptive study was to explore the medication-taking experiences of undergraduate college students prescribed short-term antibiotic therapies and to describe factors influencing their adherence. Data sources: Thirty-four undergraduate students prescribed antibiotics for treatment of an acute infectious illness at a large university health center were recruited to participate in this study. Semistructured telephone interviews were conducted after students finished their course of treatment. Qualitative descriptive content analysis was used to analyze the transcripts typed from the audio-taped phone interviews. Conclusions: The main theme that emerged from the data was antibiotic-taking self-management. Most participants were able to adapt medication regimens into their daily routines, and used events in their day and specific reminder strategies to help them to remember to take their medications. This occurred despite an ever-changing class and work schedule and being prescribed complex, lengthy antibiotic regimens. Most dosing errors occurred during times when schedules changed or students were off campus during weekends or college breaks. A small number of students discontinued therapy early because of side effects or forgetfulness. Implications for practice: By understanding factors that influence antibiotic adherence from a college student perspective, healthcare providers can suggest strategies to promote adherence that are tailored to the specific needs of this unique population. © 2006 American Academy of Nurse Practitioners.
6 citations (Crossref) [2023-10-31] Place: United States Aronson, Barbara S. Department of Nursing, Southern Connecticut State University, New Haven, Connecticut 06515, USA. aronsonb1@southernct.edu
Keywords: *Anti-Bacterial Agents/tu [Therapeutic Use]; *Patient Compliance; *Self Care; *Students; Adolescent; Adult; Anti-Bacterial Agents; Antibiotic adherence; College students; Female; Humans; Male; Medication self-management; Patient Compliance; Self Care; Students; United States; adolescent; adult; antiinfective agent; article; dept.nur; female; human; male; patient compliance; self care; student

Effectiveness of a role-modeling intervention on student nurse simulation competency - Aronson, Barbara; Glynn, Barbara; Squires, Timothy (Clinical Simulation in Nursing, 2013)
Novice nurses are often inadequately prepared to respond to complex, patient care situations where patients' conditions deteriorate. Exposure to a video-taped intervention that role-models and reinforces expected behavior of an expert nurse before participation in a simulation may improve student nurse performance in a cost-effective manner. The primary purpose of this quasi-experimental pre-test, post-test study was to assess the preliminary effectiveness of a theory based role-modeling intervention on enhancing student nurse competency in responding to a simulated response to rescue event. Performance was measured by a previously validated Heart Failure Simulation Competency Evaluation Tool (c) (HFSCET). Total mean scores on the HFSCET for the pre-test (59.08) and post-test (87.08) were significantly different (p = .000); students performed better on the post-test after exposure to the role-modeling intervention. A power analysis indicated a large effect size (effect size = .926; alpha = 0.50; power = 0.991). Students who had a greater number of days between the intervention and the post-test had a lower score. This innovative intervention based on established learning theory may change the way educators prepare novice students to achieve expected clinical competencies in graded simulation performance assessments. (c) 2013 International Nursing Association for Clinical Simulation and Learning. Published by Elsevier Inc. All rights reserved.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-811-864-193-208 tex.type: [object Object]
Keywords: Intervention; Nursing students; Performance assessment; Simulation; dept.nur

Competency assessment in simulated response to rescue events - Aronson, Barbara; Glynn, Barbara; Squires, Timothy (Clinical Simulation in Nursing, 2012)
Background: Reliable and valid instruments are needed to assess patient safety competencies, specifically nursing students' ability to appropriately respond to simulated rescue events. Methods: This was an instrument development study conducted with 152 senior nursing students in 2 phases. Results: Student groups performed poorly during the simulation scenario, with mean scores on the Heart Failure Simulation Competency Evaluation Tool ranging from 46% to 56%. Interrater reliability increased to .839 after item revision during Phase 2 of the study. Discussion: This simulation competency assessment package is ready to be tested with more diverse student groups and novice nurses in the practice setting. © 2012 International Nursing Association for Clinical Simulation and Learning.
7 citations (Crossref) [2023-10-31] Citation Key Alias: pop00146 tex.type: [object Object]
Keywords: Failure to rescue; Instrument development; Nursing students; Patient safety; Simulation; dept.nur

Assessment of nursing student's learning outcomes and employment choice after the implementation of a senior capstone course. - Rebeschi, Lisa; Aronson, Barbara (International journal of nursing education scholarship, 2009)
Many undergraduate baccalaureate nursing programs incorporate clinical emersion courses at the end of the program. Nursing capstone courses have become increasingly important in facilitating student transition into practice. However, little is known regarding the overall effectiveness of this teaching model for students, nursing programs, and clinical agencies. Previous studies revealed conflicting results about the benefits of a senior level precepted clinical experience. In this multi-method study, the authors examined student learning outcomes, perceptions, employment choice and retention following implementation of a new capstone nursing course. Results of this study indicated that a capstone course does not necessarily significantly improve scores on achievement exams or NCLEX RN first time pass rates. Nevertheless, qualitative content analysis revealed the following themes: integration, autonomy, confidence, authority, and advocacy consistent with a perceived enhanced competence in the nursing role. Data indicated that graduates often seek employment and remain at their capstone site or within their capstone specialty.
12 citations (Crossref) [2023-10-31] Place: Germany Rebeschi, Lisa. Southern Connecticut State University, USA.
Keywords: *Attitude of Health Personnel; *Choice Behavior; *Clinical Competence; *Education; Nursing; Baccalaureate/og [Organization & Administration]; *Employment/px [Psychology]; *Students; Nursing/px [Psychology]; Adult; Attitude of Health Personnel; Capstone; Choice Behavior; Clinical Competence; Clinical Competence/st [Standards]; Clinical teaching; Education; Nursing; Baccalaureate; Employment; Female; Humans; Licensure; Nursing; Male; Middle Aged; Models; Educational; Models; Nursing; New England; Nurse's Role; Nurse's Role/px [Psychology]; Nursing Education Research; Nursing Methodology Research; Nursing education; Personnel Turnover; Personnel Turnover/sn [Statistics & Numerical Data]; Preceptorship; Preceptorship/og [Organization & Administration]; Professional Autonomy; Program Development; Program Evaluation; Qualitative Research; Self Efficacy; Students; Nursing; United States; Use of preceptors; adult; article; clinical competence; decision making; dept.nur; education; educational model; employment; evaluation; female; health care quality; health personnel attitude; human; licensing; male; middle aged; model; nurse attitude; nursing education; nursing methodology research; nursing student; organization and management; personnel management; professional practice; program development; psychological aspect; qualitative research; self concept; standard; statistics

Care of the adult patient with cystic fibrosis. - Aronson, Barbara S; Marquis, Melissa (Medsurg nursing : official journal of the Academy of Medical-Surgical Nurses, 2004)
Recently published consensus statements and conference proceedings from the Cystic Fibrosis Foundation provide new direction with regard to the etiology, diagnosis, and treatment of the adult patient with cystic fibrosis (CF). Survival has improved through early diagnosis and improved treatment, and aggressive management of complications. The current state of knowledge, the most recent evidence-based treatment options, and essentials of nursing care for the adult patient with CF are outlined.
Place: United States Aronson, Barbara S. Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Cystic Fibrosis/th [Therapy]; Adult; Age Factors; Cystic Fibrosis; Cystic Fibrosis/di [Diagnosis]; Cystic Fibrosis/ep [Epidemiology]; Cystic Fibrosis/et [Etiology]; Diabetes Mellitus; Diabetes Mellitus/et [Etiology]; Diabetes Mellitus/pc [Prevention & Control]; Female; Gastrointestinal Diseases; Gastrointestinal Diseases/et [Etiology]; Gastrointestinal Diseases/pc [Prevention & Control]; Genetic Predisposition to Disease; Genetic Predisposition to Disease/ge [Genetics]; Humans; Infection Control; Infection Control/mt [Methods]; Longevity; Nurse's Role; Phenotype; Reproductive Medicine; Reproductive Medicine/mt [Methods]; Respiratory Therapy; Respiratory Therapy/mt [Methods]; Respiratory Tract Infections; Respiratory Tract Infections/et [Etiology]; Respiratory Tract Infections/pc [Prevention & Control]; Terminal Care; Terminal Care/mt [Methods]; adult; age; artificial ventilation; case report; cystic fibrosis; dept.nur; diabetes mellitus; female; gastrointestinal disease; genetic predisposition; genetics; human; infection control; longevity; methodology; nurse attitude; phenotype; reproduction; respiratory tract infection; review; terminal care; ⛔ No DOI found

Humanizing substance abuse: a theory-based educational intervention for undergraduate nursing students - Roncallo, Hannah R.; Aronson, Barbara (Journal of Addictions Nursing, 2023)
Background Healthcare providers, as well as healthcare students, have been found to harbor negative attitudes toward individuals with substance abuse disorders, impacting the care they give and subsequently creating poor patient outcomes. Purpose This study seeks to determine the effectiveness of an educational intervention, grounded in theory, toward changing nursing student attitudes regarding patients with a substance abuse disorder. Methods Nursing students participated in a teaching intervention, developed using the experiential learning theory, that utilizes modalities for each kind of learner aimed at reducing bias toward this population. The Medical Condition Regard Scale was used pre/post intervention to determine regard toward patients with the diagnosis of substance abuse. Results Student nurses maintained the least favorable attitudes toward individuals who abuse substances in comparison with patients with the diagnoses of pneumonia or gastroesophageal reflux disease; there were significant differences in attitudes toward patients who abused substances before and after participation in the educational intervention, with postparticipation attitudes being significantly more positive than attitudes before participation. Students found the educational intervention and debriefing highly satisfactory. Implications This educational intervention can provide a cost-effective, easy-to-replicate, time-efficient learning activity that could be added to undergraduate nursing curriculum.
0 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

Evaluation of the McMahon Competence Assessment Instrument for use with midwifery students during a simulated shoulder dystocia - McMahon, Erin; Jevitt, Cecilia; Aronson, Barbara (Journal of Midwifery & Women's Health, 2018)
IntroductionIntrapartum emergencies occur infrequently but require a prompt and competent response from the midwife to prevent morbidity and mortality of the woman, fetus, and newborn. Simulation provides the opportunity for student midwives to develop competence in a safe environment. The purpose of this study was to determine the inter-rater reliability of the McMahon Competence Assessment Instrument (MCAI) for use with student midwives during a simulated shoulder dystocia scenario. MethodsA pilot study using a nonprobability convenience sample was used to evaluate the MCAI. Content validity indices were calculated for the individual items and the overall instrument using data from a panel of expert reviewers. Fourteen student midwives consented to be video recorded while participating in a simulated shoulder dystocia scenario. Three faculty raters used the MCAI to evaluate the student performance. These quantitative data were used to determine the inter-rater reliability of the MCAI. ResultsThe intraclass correlation coefficient (ICC) was used to assess the inter-rater reliability of MCAI scores between 2 or more raters. The ICC was 0.86 (95% confidence interval, 0.60-0.96). Fleiss's kappa was calculated to determine the inter-rater reliability for individual items. Twenty-three of the 42 items corresponded to excellent strength of agreement. DiscussionThis study demonstrates a method to determine the inter-rater reliability of a competence assessment instrument to be used with student midwives. Data produced by this study were used to revise and improve the instrument. Additional research will further document the inter-rater reliability and can be used to determine changes in student competence. Valid and reliable methods of assessment will encourage the use of simulation to efficiently develop the competence of student midwives.
1 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000428796300010 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Article; Clinical Competence; Dystocia; Education; Nursing; Educational Measurement; Female; Humans; Infant; Newborn; McMahon Competence Assessment Instrument; Midwifery; Nurse Midwives; Observer Variation; Pilot Projects; Pregnancy; Reproducibility of Results; Shoulder; Simulation Training; Video Recording; assessment; clinical competence; competence; content validity; controlled study; correlation coefficient; dept.nur; dystocia; education; evaluation; expert system; female; human; instrument; intrarater reliability; midwife; midwifery education; midwifery student; newborn; nurse midwife; nursing education; observer variation; obstetric procedure; peer-reviewed; pilot study; pregnancy; priority journal; procedures; quantitative analysis; quantitative study; reliability; reproducibility; scoring system; shoulder; shoulder dystocia; simulation; simulation training; standards; teacher; validation study; validity; videorecording

Enhancing evidence bases for interventions in a baccalaureate program. - Aronson, Barbara S; Rebeschi, Lisa M; Killion, Susan Westrick (Nursing education perspectives, 2007)
Modifying the sequence, objectives, and research-based content for a nursing interventions course in a baccalaureate curriculum resulted in improved outcomes including enhancement of the evidence bases for nursing interventions. A mixed methods research study demonstrated better student preparation for clinical experiences and improved satisfaction with course content, consistency, and sequencing. Faculty reported improved integration of theory, research, and practice. Although grades were slightly lower in the new course, the positive outcomes greatly outweighed this expected finding. A foundation for improving the evidence bases for future nursing practice is guided by the curricular modifications described in this article.
Place: United States Aronson, Barbara S. Department of Nursing, Southern Connecticut State University, New Haven, USA. aronsonb1@southernct.edu
Keywords: *Attitude of Health Personnel; *Curriculum; *Education; Nursing; Baccalaureate/og [Organization & Administration]; *Evidence-Based Medicine/ed [Education]; *Nursing Research/ed [Education]; *Students; Nursing/px [Psychology]; Attitude of Health Personnel; Clinical Competence; Connecticut; Curricular and course development; Curriculum; Curriculum/st [Standards]; Diffusion of Innovation; Education; Nursing; Baccalaureate; Evidence-Based Medicine; Evidence-based interventions; Faculty; Nursing; Focus Groups; Health Knowledge; Attitudes; Practice; Health Services Needs and Demand; Humans; Nursing Education Research; Nursing Methodology Research; Nursing Research; Organizational Objectives; Program Evaluation; Qualitative Research; Questionnaires; Skills laboratory; Student learning outcomes; Students; Nursing; Surveys and Questionnaires; United States; article; attitude to health; clinical competence; curriculum; dept.nur; education; evaluation; evidence based medicine; health care quality; health personnel attitude; health service; human; information processing; mass communication; nursing education; nursing methodology research; nursing research; nursing student; organization; organization and management; peer-reviewed; psychological aspect; qualitative research; questionnaire; standard; ⛔ No DOI found

The Effects of a Deliberate Practice Debriefing During a Response to Rescue Patient Simulation With Undergraduate Nursing Students - Aronson, Barbara; Bell, Arleigh; Andrighetti, Tia; Meyer, Mary; Shepherd, Karen; Bambini, Deborah (Nursing Education Perspectives, 2021)
The purpose of this multisite, randomized, pretest/posttest quasi-experimental study was to compare student nurse competency, learning retention, and perceived student support after exposure to a deliberate practice debriefing versus standardized debriefing. Fifty undergraduate students participated in the complex response to rescue simulation. The intervention group had significantly higher total mean and three subscale scores on the competency tool than the comparison group, although differences in learning retention and student support were not significant. This study provides preliminary support for the effectiveness of deliberate practice debriefing to enhance students’ mastery of skills and behaviors in complex simulations.
0 citations (Crossref) [2023-10-31]
Keywords: Baccalaureate; Clinical Competence; Education; Humans; Nurses; Nursing; Patient Simulation; Simulation Training; Students; clinical competence; dept.nur; human; nurse; nursing education; nursing student; patient simulation; peer-reviewed; simulation training

Technology use and technological self-efficacy among undergraduate nursing faculty - Roney, Linda N.; Westrick, Susan J.; Acri, Mary C.; Aronson, Barbara S.; Rebeschi, Lisa M. (Nursing Education Perspectives (Wolters Kluwer Health), 2017)
AIM This study explored faculty responses to a survey about using technology to teach undergraduate nursing students. BACKGROUND Little is known regarding faculty confidence, technology use, or supports for integrating technology into nursing education. METHOD A descriptive correlational design was utilized to explore the relationship between technology use and technological self-efficacy in faculty (N = 272) who teach at Commission on Collegiate Nursing Education–accredited nursing programs. Instruments used were a sociodemographic questionnaire, the Roney Technology Use Scale, and the Technology Self-Efficacy Scale. RESULTS Participants who taught didactic content had moderate technology use as compared to those teaching didactic and clinical/laboratory who reported high levels of technology use. A weak relationship between age and technological self-efficacy (ρ =.127, p < .05) was also found. CONLUSION This research was an initial step in understanding levels of technology use and responses to this challenge by undergraduate nursing faculty.
10 citations (Crossref) [2023-10-31] Citation Key Alias: roneyTechnologyUseTechnological2017a
Keywords: Adult; Bivariate Statistics; Coefficient Alpha; Computer Assisted Instruction; Computer Literacy; Confidence; Confidence Intervals; Content Validity; Correlational Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Education Research; Education; Nursing; Baccalaureate; Educational Status; Educational Technology – Utilization; Faculty Development; Faculty Practice; Faculty; Nursing; Female; Human; Male; Middle Age; Nonexperimental Studies; Nurse Faculty; Nursing Education; P-Value; Promotion and Tenure; Questionnaires; Scales; Schools; Nursing; Self-Efficacy; Socioeconomic Factors; Students; Nursing; Baccalaureate; Summated Rating Scaling; Surveys; T-Tests; Teaching Methods; Technological Self-Efficacy; Technology; adult; age; article; clinical laboratory; controlled study; dept.nur; dept.swk; female; human; human experiment; major clinical study; male; nursing education; nursing student; peer-reviewed; questionnaire; self concept; teaching

After the gap analysis: Education and practice changes to prepare nurses of the future - Beauvais, Audrey Marie; Kazer, Meredith Wallace; Aronson, Barbara; Conlon, Suzanne E.; Forte, Pamela; Fries, Kathleen S.; Hahn, Judith M.; Hullstrung, Russell; Levvis, Meg; McCauley, Paula; Morgan, Patricia Padula; Perfetto, Linda; et al. (Nursing Education Perspectives, 2017)
AIM The purpose of the study was to describe the Connecticut Nursing Collaborative-Action Coalition’s work in identifying and addressing gaps between nursing education and practice based on the Institute of Medicine’s Future of Nursing report. BACKGROUND Massachusetts Nurse of the Future (NOF) Competencies highlight the knowledge, skills, and attitudes/behaviors required for professional nurses. Integrating these concepts into the educational system will prepare the nursing workforce to respond to current/future health care needs and population health issues. METHOD Education and practice partners in four regions conducted a gap analysis of the education to practice transition for new graduate nurses using NOF as a framework for assessment. RESULTS Gaps in competencies were similar across regions. However, each organization uniquely addressed curricular gaps to best prepare nurses of the future. CONCLUSION Curriculum improvements will provide students the advantage of being prepared for the rapid changes happening in health care. Copyright © 2017 National League for Nursing
4 citations (Crossref) [2023-10-31]
Keywords: Academic-Practice Partnership; Connecticut; Curriculum; Education; Nursing; Forecasting; Future of Nursing Competencies; Gap Analysis; Humans; Massachusetts; New Graduate Nurses; Nursing Curriculum; Nursing Education; Nursing Staff; article; curriculum; dept.nur; forecasting; health care need; human; human experiment; nursing education; nursing staff; peer-reviewed; population health; skill; student; workforce